A Woman and Eros in the Narrative Prose of Grigorije Božović - Jevtić, Jelena G. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The heroines of Grigorije Božović’s narrative prose are typified to maintain order within both the collective and the family. Their honorable and dignified needs and emotions are often subordinated to the collective good. Regardless of the dominant archetype of the mother and the housekeeper, the number of the female characters in which the archetype of a woman inspired by eros, a polyvalent and complex one, is recognized, is not negligible. This work aims to illustrate how Božović’s heroines emerge unscathed, returning to canonized frameworks after navigating the struggles of Eros and Thanatos, how they are subject to the power of instinct, and how Eros is transformed into a religious archetype.
Keywords: Eros; archetype; Thanatos; social norms; transformation; desacralization